Contemporary Transformation of Islamic Marriage Services Through the MyNikahNow Application in the United Kingdom - Adam Adesina Muhammad-Lawal; Novia Yuriska; Linda Sari Bulan Siregar; Faisal Efendi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study addresses the contradiction between the rapid digitalization of social and administrative services and the limited modernization of Islamic marriage systems in the United Kingdom. Conventional marriage registration often lacks efficiency, accessibility, and transparency, creating challenges for couples seeking both administrative and religious validation. Therefore, the purpose of this study is to analyze the contemporary transformation of Islamic marriage services through the MyNikahNow application, which integrates digital innovation with Islamic legal principles to improve service effectiveness and legitimacy. This research employs a qualitative descriptive–analytical design. The data sources include primary materials, such as interviews with users, Islamic law scholars, and certified marriage officers, as well as secondary materials derived from official documents and academic studies. Data collection techniques involve documentation, online observation, and semi-structured interviews, while data analysis is conducted through thematic interpretation to identify patterns of technological, legal, and social transformation in digital marriage practices. The findings show that MyNikahNow effectively enhances administrative efficiency, reduces errors, and strengthens compliance with Sharia law. The application also bridges traditional religious norms with contemporary digital innovation, offering a new paradigm in managing Islamic marriages within Western contexts. This novelty demonstrates that faith-based services can adapt to digital modernization while maintaining legal and moral integrity. This study contributes to the development of digital Islamic family law and religious governance models. It recommends future research to explore comparative applications in other regions to enhance the inclusivity, sustainability, and contextual relevance of digital Islamic marriage systems.